The Reinforced Soil Wall Construction with High Stiffness Geocomposite Reinforcement and Betoflor Segmental Block, Pengerang, Johor Darul Ta’zim - Kwan Shen Tong; Weng Soon Tan (Himpunan Ahli Teknik Tanah Indonesia, 2023)
Pengerang is a municipality in Kota Tinggi district in Johor at the southern tip of the Peninsular Malaysia. It is home for the mega oil and gas hub Pengerang Integrated Petroleum Complex (PIPC) in Southern Johor state, which is one of the region’s largest hubs for oil and gas, petrochemical industries, oil storage and trading activities. The area is experiencing significant development, both residential and commercial in nature. In this development plan, the retaining wall system plays a crucial role in providing a larger development area, enhancing the aesthetic view, and achieving a higher elevation platform. The focus of this paper is on an internally stabilized reinforced soil wall system which involves reinforcing the soil with high stiffness geocomposite reinforcement and utilizing modular segmental blocks as facing elements. This combination creates a 1 vertical: 0.14 horizontal gradient (82°) wall that is implemented for a mixed development at Pengerang. The single-tier reinforced soil wall reaches a height of 13 m. In addition, the maximum 14 m high wall was designed as a two-tier wall and the maximum 19 m high wall was designed as a three-tier wall. The design of the reinforced soil wall includes the evaluation of various potential internal and external failure modes. This paper also discusses the construction sequences employed for the reinforced soil wall. Ultimately, the combination of the high stiffness geocomposite reinforcement with modular segmental blocks has proven successful, resulting in a constructed wall that satisfied the client requirements